A Journey to Understand Enjoyment in Academic Writing - Kristin K Janke; Bethany Von Hoff; Eliza Dy-Boarman (University of Minnesota Libraries Publishing, 2018)
To assist academic writers in finding enjoyment in writing, this paper draws a distinction between enjoying the process of writing and enjoying the nature of writing.  Based on an examination of academic writing literature, analysis of personal experiences, and a review of the positive psychology literature, conditions that support writing enjoyment are posited.    Readers are invited to examine their personal experience with writing enjoyment relative to these levers.  Concrete actions for authors to improve enjoyment in writing are suggested based on the theories discussed, including actions to support flow, creativity, curiosity, courage, mindset, purpose, and humility. Article Type: Commentary